Powderpost Beetles and Other Wood-Infesting Insects - P.G. Koehler (EDIS)
This document provides an overview of powderpost beetles and other wood-infesting insects, detailing their identification, life cycles, and the damage they cause to wooden structures. It covers the most common types, including anobiine, lyctine, and bostrichid beetles, as well as old house borers and carpenter bees. The article emphasizes the importance of early detection and control, outlining various prevention and treatment methods such as surface treatments, wood replacement, and fumigation. It also highlights the significance of proper wood inspection and finishing to prevent infestations.